2020
DOI: 10.1136/bmjdrc-2019-001130
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and costs of cardiovascular events in Spanish patients with type 2 diabetes mellitus: a comparison with general population, 2015

Abstract: IntroductionCardiovascular (CV) disease affects a high percentage of patients with type 2 diabetes mellitus (T2DM), especially in the hospital setting, impacting on mortality, complications, quality of life and use of health resources. The aim of this study was to estimate the incidence, mean length of hospital stay (LOHS) and costs attributable to hospital admissions due to CV events in patients with T2DM versus patients without diabetes mellitus (non-DM) in Spain.Research design and methodsRetrospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…A review by the Health Technologies Assessment Agency of Spain confirmed that the major components of the costs of T2DM were hospitalization (10-67%) and costs of medication for T2DM complications (14-33%) [81], results also reported by the previously mentioned Mata-Cases et al study in Catalonia [43]. Further, a recent study demonstrated that the length of hospital stay was longer for patients with T2DM, compared with patients without diabetes, for non-fatal acute myocardial infarction and unstable angina, resulting in higher hospitalization costs [82].…”
Section: Discussionsupporting
confidence: 54%
“…A review by the Health Technologies Assessment Agency of Spain confirmed that the major components of the costs of T2DM were hospitalization (10-67%) and costs of medication for T2DM complications (14-33%) [81], results also reported by the previously mentioned Mata-Cases et al study in Catalonia [43]. Further, a recent study demonstrated that the length of hospital stay was longer for patients with T2DM, compared with patients without diabetes, for non-fatal acute myocardial infarction and unstable angina, resulting in higher hospitalization costs [82].…”
Section: Discussionsupporting
confidence: 54%
“…A statistical power analysis considering the proportion of patients with T2D suffering from CVD in our study population (35.6%) was performed. The scientific literature corroborates this proportion describing a mean prevalence of 32.2% of CVD in patients with T2D worldwide ( 20 , 21 ). Considering our sample comprises 46 T2D patients with CVD and 83 T2D patients without prevalent CVD our statistical power is >85% (e.g., 87.7%).…”
Section: Methodssupporting
confidence: 52%
“…In the same year, five million deaths were attributed to DM, and worldwide 850 billion US dollars were spent on managing the disease [ 2 ]. The costs arising from DM are mainly due to the associated complications, chief among which are ischemic heart disease, stroke, diabetic foot and diabetic nephropathy [ 3 , 4 ]. Socioeconomic factors such as gender, age, education, type of health insurance and the time of evolution since diagnosis are significantly associated with disease outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%